Una Murray on Smallholder women's empowerment through participatory design and user-led innovation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Smallholder women's empowerment through farmer-participatory design and user-led innovation of labour-saving tools in Malawi Presentation by Una Murray, from National University of Ireland Galway, at the seminar on Closing the gender gap in farming under climate change held 19 March 2015 in Paris. Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action